Medulloblastoma Presenting With Pure Word Deafness: Report of One Case and Review of Literature - Yen-Ting Chou; Po-Wu Liao; Michael Che-Hung Lin; Jih-Chyun Chou; Yung-Hsiu Lin; Ming-Hung Lin; Sai-Hung Tang; Mei-Huei Chen (Pediatrics and Neonatology)
Pure word deafness (PWD) is a rare disorder characterized by impaired verbal comprehension sparing discrimination and recognition of nonverbal sounds with relatively normal spontaneous speech, writing, and reading comprehension. Etiologies of this syndrome are varied, and there are rare reports about brain tumor with PWD in children. We report a case of medulloblastoma presented with PWD in a 7-year-old girl. She visited our outpatient clinic because of English dictation performance deterioration. PWD was diagnosed by the otolaryngologist after examinations. Posterior fossa tumor and obstructive hydrocephalus were shown in the magnetic resonance imaging of the brain. The diagnosis of medulloblastoma was then made by pathology.